Psychological interventions as vaccine adjuvants: A systematic review. Issue 25 (31st May 2019) - Vedhara, Kavita; Ayling, Kieran; Sunger, Kanchan; Caldwell, Deborah M.; Halliday, Vanessa; Fairclough, Lucy; Avery, Anthony; Robles, Luke; Garibaldi, Jonathan; Welton, Nicky J.; Royal, Simon
Highlights: Psychological factors have been show to alter the human immune response to vaccines. We explore if psychological interventions can enhance the immune response to vaccines. Trial results suggest such interventions may improve antibody responses to vaccines. However, intervention effects varied between outcome measures and over time. Abstract: Objectives: The effectiveness of vaccines is known to be altered by a range of psychological factors. We conducted a systematic review to evaluate the effects of psychological interventions on the ability of vaccines to protect against disease, as measured by antibody responses. Methods: Electronic databases (EMBASE, Medline, PsychINFO, CINAHL) were searched from their inception to 6th February 2018. Results: The search yielded 9 eligible trials conducted with 1603 participants and four broad categories of intervention: meditation/mindfulness (n = 3), massage (n = 3), expressive writing (n = 2) and cognitive behavioural stress management (n = 1). Some evidence of benefit on the antibody response to vaccination was observed in 6/9 of all trials and in 4/7 of randomised controlled trials. However, effects on antibody levels were often mixed, with only 3 of 6 trials showing benefit demonstrating an improvement in all antibody outcomes and at all time points assessed. Trials demonstrating benefit also provided direct or indirect evidence of adequate adherence with the intervention; and in 50% of these trials, there was also evidence that the intervention was effective in changing the mediating psychological constructs targeted by the intervention. Conclusions: This literature is characterised by considerable heterogeneity in terms of intervention type, vaccine type, age of participants and the temporal relationship between vaccination and intervention. We conclude that there is early evidence to suggest that psychological interventions may enhance the antibody response to vaccination. However, the effects are inconsistent, with the greatest likelihood of benefit seen in trials evidencing adequate adherence with the intervention. Future work would benefit from rigorous intervention development that focuses on achieving adequate adherence and large well-controlled randomised trials with a focus on an agreed set of outcomes.